2001
DOI: 10.1038/88903
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of donor genome in cloned bovine embryos

Abstract: Despite recent successes in cloning various animal species, the use of somatic cells as the source of donor nuclei has raised many practically relevant questions such as increased abortion rates, high birth weight and perinatal death. These anomalies may be caused by incomplete epigenetic reprogramming of donor DNA. Genome-wide demethylation occurs during early development, 'erasing' gamete-specific methylation patterns inherited from the parents. This process may be a prerequisite for the formation of pluripo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
352
3
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(389 citation statements)
references
References 23 publications
21
352
3
13
Order By: Relevance
“…Similar results were also found in mouse [20]. In cloned bovine embryos, these repeated regions of the donor genome exhibited aberrant methylation patterns [8]. In our study, the aborted cloned pigs showed aberrant high levels of methylation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were also found in mouse [20]. In cloned bovine embryos, these repeated regions of the donor genome exhibited aberrant methylation patterns [8]. In our study, the aborted cloned pigs showed aberrant high levels of methylation.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies demonstrated that the majority of imprinted genes play important roles in regulating the normal development of the fetus and placenta, and the expression of these genes is regulated by the methylation status of the promoters [5,6]. Numerous studies reported that aberrant DNA methylation occurs in cloned mammalian embryos [7,8]. PRE-1, a short interspersed nucleotide element (SINEs), has 10 5 copies in porcine genome, whereas centromeric satellite DNA is a highly repetitive sequence in porcine heterochromatic region.…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions may result in both de novo methylation and demethylation of specific loci of donor nuclei, which may occur stochastically, resulting subsequently in aberrant patterns of gene expression and failure of development. In one recent study, the methylation status of the donor nucleus at the blastocyst stage was found to be either unchanged or aberrant compared to the control 59 . Reprogramming of the X chromosome can occur, however, as the inactive X chromosome can be reactivated in the somatic nucleus, although the molecular memory of the inactive X chromosome is retained, resulting in its preferential inactivation in the trophectoderm 60 .…”
Section: Reprogramming Somatic Nuclei In the Oocytementioning
confidence: 99%
“…Several groups have investigated DNA methylation patterns in NT embryos and reported abnormalities in DNA methylation (Dean et al, 1998BourcЈhis et al, 2001;Kang et al, 2001aKang et al, , 2002Ohgane et al, 2001). In cloned bovine embryos, satellite sequence methylation levels are more similar to the donor cells than to control embryos (Kang et al, 2001a).…”
Section: Dna Methylation and Ntmentioning
confidence: 99%
“…These findings suggest that different chromosomal regions might respond differently to demethylation in the egg cytoplasm. Of interest, when satellite sequences that had been examined in bovine (Kang et al, 2001a) were analyzed in a different species (porcine) methylation levels at the blastocyst stage of cloned embryos were more comparable to those of fertilized control embryos (Kang et al, 2001b), suggesting also species-specific differences. A recent study that analyzed several imprinted genes in cloned murine blastocysts showed that most of the examined genes displayed aberrant methylation and expression patterns (Mann et al, 2003).…”
Section: Dna Methylation and Ntmentioning
confidence: 99%